Digital design - M. Morris Mano
Binary systems-- Boolean algebra and logic gates-- Simplification of boolean functions-- Combinational logic-- MSI and PLD components-- Synchronous sequential logic-- Registers, counters, and the memory unit-- Algorithmic state machines (ASM)-- Asynchronous sequential logic-- Digital integrated circuits-- Laboratory experiments-- Standard graphic symbols